PEMBELAJARAN IPS MENGGUNAKAN MODEL KOOPERATIF TIPE THINK PAIR AND SHARE DI SEKOLAH DASAR - wati, ilda; Arwin, Arwin; Lubis, Mansur (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this research is to describe the improvement of the students’ learning outcomes of the subject Social Science by using the TPS type of the coorperative model at SDN 25 Lubuk Alung Padang Pariaman. The design of the research was class action research. The subject were a teacher and 32 fifth graders of the school. It was found that the score of the lesson plan increased from 80,37% in cycle I to 96,42% in cycle II. In term of the teacher’s aspect, the score increased from 78,13% in cycle I to 93,75% in cycle II. Meanwhile, in term of the students’ aspect, the score increased from 70,31% in cycle I to 87,5% in cycle II. Finally, the average score of the students’ learning outcomes increased from73,43 in cycle I to 78,15 in cycle II.